Proposed Information System Design to Support Catalog Information in Construction Services at PT XYZ - Bima Pramono Aji (Eduvest - Journal of Universal Studies, 2025)
The construction sector continues to face challenges related to project cost efficiency, especially during the procurement phase. At PT XYZ, this issue stems from the absence of an integrated catalog information system for pricing and contracts. Consequently, budget planning, vendor selection, and procurement assessments lack reliable historical data. Disparate pricing data across departments and insufficient integration with ERP SAP reduce the accuracy of budget formulation and decision-making. This study aims to: (1) ascertain developmental requirements for a catalog information system based on ideal conditions and root cause analysis; and (2) devise a system design to support data-driven procurement decisions. The research employs the System Development Life Cycle (SDLC) methodology, starting with preliminary research to investigate underlying causes, followed by gap analysis, technical information assessment, and system design through Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). The database is structured according to Third Normal Form (3NF) to ensure data efficiency and integrity. The findings show that the proposed catalog system integrates centralized price databases with ERP SAP, incorporates vendor evaluation mechanisms, establishes standardized data templates, and implements price trend analysis features. The resulting system is expected to enhance the accuracy and consistency of procurement decisions by providing historical data access, vendor performance tracking, and automated price simulations. This research contributes to procurement digitization practices in the construction industry by offering a systematic framework for implementing integrated catalog information systems that improve cost efficiency, transparency, and planning quality in construction projects.